The Names of Heaven and Hell in the Glorious Qur’an and their Worship of Allah Almighty -A Doctrinal Study - (Islamic Sciences Journal, 2025)
ABSTRACTI divided this research (The Names of Paradise and Hell in the Glorious Qur’an and Their Worship of Allah Almighty - A Doctrinal Study) into two sections, preceded by an introduction. In the first section, I dealt with: (The definition of servitude in language and terminology, and the definition of Paradise and Hell in language and terminology). I divided this section into three demands. In the first demand, I dealt with: The definition of servitude in language and terminology. In the second demand, I dealt with: (The names of Paradise and Hell in the Glorious Qur’an, and the evidence of the servitude of Paradise and Hell to Allah Almighty). I divided this section into four demands. In the first demand, I dealt with: The names of Paradise in the Glorious Qur’an. In the second demand, I dealt with: The names of Hell in the Glorious Qur’an. In the third demand, I dealt with: The evidence mentioned in the servitude of Paradise from the authentic Prophetic Sunnah. In the fourth demand, I dealt with the evidence mentioned in the servitude of Hell from the Glorious Qur’an and the authentic Prophetic Sunnah. Then I concluded with the most important results I reached in this research, followed by sources and references.
Keywords: Heaven, Hell, Slavery, Abode of Peace, Abode of Eternity